Genome Analysis Reveals Diversity and Functional Potential of Novel Janthinobacterium Species From Subarctic Soils - Kumar, Anil; Männistö, Minna K.; Kerkhof, Lee J.; Häggblom, Max M. (Wiley-Blackwell, 2026)
The Arctic tundra and boreal forest regions are affected by ongoing climate change, leading to increased warming, increased plant production, and heightened microbial activity. Microbes play a key role in carbon release from stored soil organic matter, and characterizing their diversity and function in high-latitude soils is thus of significant interest. The Pseudomonadota are abundant and diverse members of high-latitude soils. Here, we describe two novel species of the genus Janthinobacterium, of the order Burkholderiales, isolated from tundra heath and northern boreal forest soils. The isolates are aerobic, chemoorganotrophic psychrophiles and are well-adapted to the subarctic climate conditions. Phylogenomic analyses and ANI values confirmed the novelty of the strains, designated as Janthinobacterium silvisoli sp. nov. K2Li3 and Janthinobacterium saanense sp. nov. S3T4. Genome analysis revealed that the new species have the metabolic potential for degradation of complex carbon and polyphenols, which are abundant in tundra heath and lichen-dominated, nutrient-poor forest soils. The strains are well-adapted to nitrogen-limited soil ecosystems and can scavenge nitrogen from both organic and inorganic sources. Additionally, the strains harbor secondary metabolite gene clusters that encode antimicrobial compound production, potentially enhancing their competitiveness in the subarctic environment. The comparative pangenome analysis indicated that the strains have unique gene clusters for carbohydrate transport and metabolism, and energy generation and conservation. The genome-based functional exploration enhances our understanding of this genus and how environmental conditions may shape the functionality and interactions of Janthinobacterium species in subarctic soil ecosystems.
Keywords: cold-adapted; novel species; subarctic ecosystem